A dual‐band single‐layer circularly polarized reflectarray composed by elements having variable rotation angles. Issue 1 (19th May 2014) - Zhong, Xian‐Jiang; Chen, Lei; Shi, Yan; Shi, Xiao‐Wei
ABSTRACT A dual‐band single‐layer circularly polarized reflectarray composed by elements with variable rotation angles is presented in this article. Orthogonal dipole elements etched on the substrate are designed to operate at 10 and 13.5 GHz, respectively. By introduction of element rotation technique, the proposed reflectarray has a good isolation between the two operating bands and obtains excellent performance of circular polarization compared with the conventional design. All the simulated and measured results demonstrate the advantages of the proposed reflectarray. © 2014 Wiley Periodicals, Inc. Int J RF and Microwave CAE 25:39–47, 2015.